Occupational mismatch of immigrants in Europe: The role of education and cognitive skills - Merve Cim; Michael Sebastian Kind; Jan Kleibrink (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
Occupational mismatch is a wide-spread phenomenon among immigrants in many European countries. Mismatch, predominantly measured in terms of education, is often regarded as a waste of human capital. Such discussions, however, ignore the imperfect comparability of international educational degrees when comparing immigrants to natives. An accurate analysis of occupational mismatch requires looking beyond internationally incomparable educational degrees and considering more comparable skill measures. Using PIAAC data, it is possible to exploit internationally comparable cognitive skill measures to analyze the presence of mismatch disparities between immigrants and natives. This allows us to examine whether overeducation implies only an apparent phenomenon or rather a genuine overqualification observed also in the form of cognitive overskilling. In this study, we analyze differences in the incidence of being overeducated and being cognitively overskilled between immigrants and natives in 11 European countries. Results show that immigrants are more likely to be overeducated than natives, while the opposite is true for being cognitively overskilled. Furthermore, significant heterogeneity among immigrants in the incidence of overeducation and cognitive overskilling can be detected. – – Mangelnde Kongruenz von Arbeitnehmern und ihren Berufen ist in Europa ein unter Immigranten weit verbreitetes Phänomen. Diese Diskrepanz wird meist durch Bildung gemessen und als eine Verschwendung des Humankapitals interpretiert. Diese Argumentation vernachlässigt jedoch die eingeschränkte Vergleichbarkeit von internationalen Bildungsabschlüssen. Eine akkurate Analyse der Diskrepanz erfordert daher international vergleichbare Maßstäbe zur Messung von Qualifikationen. Mit Hilfe der international vergleichbaren Fragebögen der PIAAC Daten ist es möglich, die unterschiedlichen Qualifikationen von Migranten und einheimischen Beschäftigten über die Bildungsabschlüsse hinaus zu vergleichen. Dadurch können wir untersuchen, ob Überqualifikation nur ein fiktives Phänomen ist, oder tatsächlich auch auf Ebene der kognitiven Fähigkeiten vorliegt. In dieser Studie beschäftigen wir uns mit Bildungs- und Qualifikationsunterschieden zwischen Migranten und Einheimischen in elf europäischen Ländern im selben Beruf. Die Ergebnisse zeigen, dass Migranten im Vergleich zu Einheimischen für ihre Berufe häufig unverhältnismäßig gut gebildet sind, jedoch dass das Gegenteil für kognitive Fähigkeiten zutrifft. Darüber hinaus können wir eine signifikante Heterogenität zwischen Immigranten im Auftreten beider Messgrößen feststellen.
Keywords: I21; J15; J24; J71; 330; Occupational mismatch; migration; education; cognitive skills